Effect of Thawing Technique on the Quality and Status of Acrosome Reactions - Safitri, Brilla Ismaya; Wahjuningsih, Sri; Yekti, Aulia Puspita Anugra; Susilawati, Trinil (Universitas Halu Oleo, 2022)
The success of Artificial Insemination is affected by the thawing technique used by the inseminator. The difference in thawing technique can affect the quality of the spermatozoa produced. This study aims to determine the effect of temperature and duration of thawing on the frozen semen quality of Bali and Madura cattle. The material used was 80 frozen semen straws for Bali cattle and Madura cattle. The method used is an experiment with four treatments and 10 replications, that is thawing in water at 37℃ for 30 seconds duration, 28℃ for 30 seconds, 28℃ for 45 seconds and 28℃ for 60 seconds. The variables observed in this study were capacitation, intact acrosome, intact plasma membrane and chromatin damage. The data were analyzed using a Randomized Block Design with replication as a block. The results of the analysis of variance showed that thawing technique had significant effect (p<0.05) on not yet capacitated, intact acrosome, intact plasma membrane. Thawing technique had no significant effect (p>0.05) on the acrosome reacted and chromatin damage.Keywords: thawing technique, capacitation, intact acrosome, intact plasma membrane, chromatin damage